THE PURPOSE, TASKS AND SOURCES OF INFORMATION FOR THE ANALYSIS OF THE MOVEMENT OF FUNDS - Djoʻrayev Davlat Djonibekovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Construction is one of the main sectors of the economy of the Republic of Uzbekistan, as a result of which new and existing capital funds (buildings, structures, machines, equipment) are created. ' and resources) plays an important role. The main goal of analyzing the movement of funds of enterprises and organizations is to obtain general information about the future state of the enterprise, and it is necessary to have information about the funds of the enterprise, that is, working capital. To find out, it is determined by analyzing the information in the cash flow statement.